2015
DOI: 10.1007/s10753-015-0201-6
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-CpG-Binding Protein 2 (MECP2) Polymorphism in Iranian Patients with Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease which involves many organs and presents with various symptoms. It has been shown that genetic and environmental factors play a major role in this disease and may affect the onset, activity, damage, and mortality of the disease. According to recent studies, methyl-CpG-binding protein 2 (MECP2) has been associated with SLE in various populations. Herein, we studied MECP2 polymorphism in Iranian lupus patients and controls. The study included a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…We noticed that the below mentioned polymorphisms like rs2075596 G/A, rs1734787 C/A, rs17435 A/T and rs2239464 G/A within MECP2 gene are more widespread in SLE patients than in healthy controls. These observations are consistent with those made by Alesaeidi et al [33] in Iranian population, Webb et al [7] in European, Sawalha et al [5] in Korean and also by Kaufman et al [8] in four different populations. Bentham et al revealed in his GWAS analysis that MECP2 rs1734787 is an appropriate SLE risk factor for people of European ancestry [45].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We noticed that the below mentioned polymorphisms like rs2075596 G/A, rs1734787 C/A, rs17435 A/T and rs2239464 G/A within MECP2 gene are more widespread in SLE patients than in healthy controls. These observations are consistent with those made by Alesaeidi et al [33] in Iranian population, Webb et al [7] in European, Sawalha et al [5] in Korean and also by Kaufman et al [8] in four different populations. Bentham et al revealed in his GWAS analysis that MECP2 rs1734787 is an appropriate SLE risk factor for people of European ancestry [45].…”
Section: Discussionsupporting
confidence: 93%
“…There is little research in the literature specific MECP2 polymorphisms with SLE activity or severity. Alesaidi et al [33] demonstrated no significant association between rs1734791, rs1734787 in MECP2 and clinical features. Doudar et al [34] also did not detect significant relationship between rs1734791 in MECP2 and disease severity or activity.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast to our results, the T allele of the rs1734791 SNP was identified as a lupus risk allele in two other studies. One of them was conducted by Alesaeidi et al [13] on the Iranian population; however they also reported no significant association between the genotype frequency of this SNP and the risk of SLE and no correlation of this SNP with clinical manifestations of SLE…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) in MECP2 and IRAK1 genes have been independently associated with risk of SLE in Asian and European populations [8, 1113]. However, similar studies in the Egyptian population are not available yet.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that there were significant correlations between rs1734787 and rs1734791 polymorphisms of MECP2 and SLE progression among Iranian patients in which the C allele of rs1734787 and T allele of rs1734791 polymorphisms increased the SLE risk. Moreover, there were significant frequencies of CTAT and AAAT haplotypes in cases and controls, respectively [76].…”
Section: Cytokinesmentioning
confidence: 97%